DE-RADICALIZATION AND GUIDANCE FOR CRIMINAL ACTS OF TERRORISM IN INDONESIA - Dewa Ayu Putu Utari Praba (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2020)
Deradicalization is an effort to reduce radical activities and neutralize radical understanding for someone who is involved with terrorists and their sympathizers and community members who are exposed to radical terrorist understandings. These efforts to transform from radical beliefs or ideologies to non-radical ones with multi and interdisciplinary approaches for people who are affected by radical beliefs. However, in this case the de-radicalization program against terrorism has not been effective due to several things such as the non-optimal implementation of existing development standards, community culture that is sometimes still relatively difficult to accept ex- terrorists after they leave prison, as well as non-cooperative prisoners. In this case, the handling of Terrorism Crimes committed by the government can be divided into two fields, inside the Penitentiary and outside the Penitentiary. The legal approach method based on Law Number 15 of 2003 concerning Eradication of Terrorism Crimes has not optimally reduced the potential for violence against acts of terrorism because it tends to display the use of weapons. This research was conducted using an empirical legal research method that combines descriptive qualitative and quantitative methods. The nature of this research is descriptive research (describing) analysis. With the efforts to deradicalize and foster terrorism, it is hoped that there will be cooperation between terrorist prisoners and the government to provide information on the existence of the terrorism network.